Bi-level Problem with Facility Allocation for Evacuation Planning - Khanal, Durga Prasad; Pyakurel, Urmila; Dhamalab, Tanka Nath; Dempec, Stephan (GANIT: Journal of Bangladesh Mathematical Society, 2024)
At the time of evacuation, placement of the facilities for the support of evacuees is an important task. The proper allocation of the facilities in such a way that the reduction in the flow value due to the placement of facilities on the arcs is minimal, is another important aspect of the problem. In this paper, we introduce an evacuation planning problem with facility allocation by using bi-level formulation. The upper level problem identifies the best possible location and lower level problem finds the optimal solution in the network with facility allocation. We solve the problem with a naive approach of combinatorial optimization and the Karush-Kuhn-Tucker (KKT) transformation. J. Bangladesh Math. Soc. 44.2 (2024) 017–027